Mendorong Praktik Lingkungan Berkelanjutan melalui Pengelolaan Sampah Berbasis Partisipasi Komunitas di Ngepet - Adiluhung, Yusgiantoro; Aldwoah, Malak Khaled Ahmed; Abimanyu, Pradipa; Misbah, Muhammad Fauzi; Yazid, Rafi; Latifiah, Nanda Putri; Andini, Meidhita; Febriani, Shakeela; Meylani, Vivin; Fauziah, Kholifatul (Universitas Muhammadiyah Yogyakarta, 2025)
Ineffective waste management in Dukuh Ngepet, Srigading, Sanden, Bantul, has caused negative impacts on the environment, including soil and water pollution and increased public health risks. This community service aims to implement an integrated waste management system based on community participation to increase public awareness and involvement in sorting and processing waste more responsibly. Need of assessment shows that the community faces difficulties in sorting waste due to limited facilities and a lack of understanding of proper waste management. This was revealed through interviews and Focus Group Discussions (FGD) with local stakeholders. This community service uses a participatory method that involves direct observation, interviews with the community, and the implementation of a waste sorting socialization and training program. In its implementation, the community is given education about sorting organic, inorganic, and B3 waste, and is provided with facilities in the form of sorting trash bins to assist the waste management process. The results of community service show that after the implementation of the program, there was an increase in public awareness of the importance of sorting waste, as indicated by a reduction in the volume of household waste by 26.73%. In addition, the community becomes more skilled in processing organic waste into compost and recycling inorganic waste to reduce the amount of waste disposed of in landfills. To ensure the sustainability of the program, support from local regulations and continued assistance are needed so that the community remains consistent in implementing an integrated waste management system. This program emphasizes that a community-based approach can be an effective solution in creating a cleaner and more sustainable environment.